Surgical Treatment of Intervertebral Hernias - Isakov B.M; Isakov K.B; Mirzayuldashev N.Yu; Mamadzhanov K.H (Genius Journals, 2022)
The paper analyzes the manifestations of lumbar intervertebral hernias in 426 patients undergoing surgical treatment for this reason. The main determining indication for the operation was a pronounced radicular pain syndrome. Some sexual and age-related features of localization and clinical manifestations of lumbar hernias were revealed, as well as a fairly frequent combination of the latter with the phenomena of instability of the corresponding vertebral-motor segment (PDS) - in almost a third of patients with discradicular conflict. The operation of choice for this pathology is the intervertebral microsurgical removal of a herniated disc
Keywords: Lumbar Intervertebral Hernias; Mini Access; Interlaminar Access; Arcotomy